Exceptionally broad HIV-1 neutralization via bispecific antibody–mediated prepositioning - Soohyun Kim; Katie A. Travisano; Bailey Wilder; Martina Palomares; Zheng Cao; Michael S. Seaman; Peter S. Kim (Proceedings of the National Academy of Sciences, 2025)
Antibodies that recognize the conserved prehairpin intermediate (PHI) of class I viral membrane-fusion proteins typically show limited neutralization and have not been considered promising therapeutic agents. We previously developed a bispecific antibody (bsAb), iMab/D5_AR, directed toward both the gp41 N-heptad repeat (NHR) that is exposed within the HIV-1 PHI and toward CD4, the HIV-1 receptor on T cells. CD4-binding led to prepositioning of the bsAb at the site of viral fusion, enhancing its neutralization potency and achieving 95% breadth (IC80 < 5 μg/mL) against a panel of 119 pseudotyped, multiclade HIV-1 viruses. In the current study, we engineered a bsAb against NHR that also targets CCR5, one of two HIV-1 coreceptors on T cells. This optimized bsAb design further improves neutralization potency and achieves 100% neutralization breadth against the 119-member pseudotyped virus panel, including those resistant to CD4-binding iMab/D5_AR. Considering that nearly all initial HIV-1 infections occur via CCR5-tropic viruses, we expect our redesigned bsAb targeting CCR5 to be an effective prophylactic agent. These findings further support the rationale for pursuing the NHR as a therapeutic target for HIV-1 and lay the groundwork for a new class of engineered broadly neutralizing antibodies.